체육교과 진화에 관한 생태학적 조망 - 김재운(Chae-Woon Kim); 이주욱(Joo-Wook Yi) (한국콘텐츠학회 논문지, 9(2), 2009)
This study purports to review and discuss the evolution of Physical Education in terms of ecological viewpoint. To achieve this purpose, this study try to look for the meanings through the 2007 revised physical education curriculum. The reason that I look for the meanings from the curriculum is because the curriculum includes objectives, values and philosophical backgrounds in Physical Education. Through this study, I found the following results. Governmental active supports to reinforce roles of in-service teachers should be emphasized. Second, teacher should focus on Game strategies for Physical Education. Third, mental function for activities in Physical Education should be considered as an intelligence as one of H. Gardner's multiple intelligences rather than they are just accepted as the level of functions or a motor nerves. Fourth, Physical Education for 11 and 12 grades should be accepted as a requirement to maintain Physical Education. classes in high school as a normalization process. 본 연구는 체육교과 진화에 관해 생태학적으로 조망해 보고 논의 하는데 그 목적이 있다. 이를 위해 2007년 개정 체육과 교육과정을 통해서 의미를 모색해보았다. 교육과정을 토대로 체육교과의 진화를 조망한 이유는 개정 체육과 교육과정에는 체육교육의 목표, 가치, 체육교육의 철학적 배경을 담고 있기 때문이다. 본 연구를 통해 타나난 결과는 다음과 같다. 첫째, 현장교사에 대한 역할 강화를 위한 적극적 지원이 강조되어야 한다. 둘째, 체육교과에서 전술이 강조되어야 한다. 셋째, 운동을 단순히 기능 혹은 운동신경수준이 아닌 가드너가 제시한 지능으로 해석하는 것이 필요하다. 넷째, 체육교과의 정상화를 위해서는 현재 고등학교 2, 3학년에서 체육교과 필수 지정에 대한 노력이 필요하다.